HUMAN RESOURCE PRACTICES AND HUMAN CAPITAL: EVIDENCE FROM INDIAN MANUFACTURING SECTOR - Solkhe, Ajay; Muchhal, Devender Singh; Singh, Vikram (PEARSON JOURNAL, 2021)
Human Capital plays the most vital role to any organization for achieving diversified business goals in today’s scenario. Also, the HR practices followed in Indian organization plays a very crucial role for the organizational success. The present study was designed to study the nature and pattern of relationship between Human Capital and HR practices (Compensation, Performance Evaluation process & promotion) of the employees working in manufacturing sector. Questionnaires consisting of 19 items (Human Capital) and 15 items (HR Practices) were used. The findings of the present study reveals that Human Capital followed in Indian Industry are correlated positively with the HR Practices.